PERILAKU IBU TERHADAP KEJADIAN PENYAKIT CAMPAK DI WILAYAH KERJA PUSKESMAS LABUHAN DELI KABUPATEN DELI SERDANG SUMATERA UTARA TAHUN 2016 - Bernadetta Ambarita (Elisabeth Health Jurnal, 2017)
Measles is a contagious disease that poses a health problem in infants and children in Indonesia and is a disease that can be prevented by immunization, measles immunization managed to lose 15.6 million (75%) of measles deaths worldwide .In Puskesmas Labuhan Deli immunization against measles in 2014 has almost reached the target of 89.6% whereas in 2015 measles immunization rates of 98.6%, the incidence of measles in 2014 does not exist, but in 2015 the measles of 4 people. Goals : The purpose of research To analyze the Behavior Mothers Against Measles disease events in Puskesmas Kecamatan Labuhan Deli Serdang 2016. Methods : The method used qualitative phenomenological approach. Subject of research that mothers of children with measles who are domiciled in the District Labuhan Deli 2016 with data collection snowball sampling. Data were collected through interviews and documentation study. Data analysis Colaizzi approach. Result : The results showed maternal knowledge about measles is still low. Mother's attitude toward the incidence of measles 2 positive outlook and 2 negative view .Action mother in the incidence of measles is not in accordance with the handling of measles. Conclution : Based on the research, suggested to the family to provide support to mothers in order to pay more attention to their children's health, and the health professionals in order to provide education on immunization against measles and measles.